Efeito da fermentação na qualidade físico-química e sensorial do café arábica variedade catuaí amarelo (Coffea arabica) - Vaz, Carlos Johnantan Tolentino (2021)
Arabica coffee is one of most expression agricultural products on national commodities market and has a great importance on national trade balance and it’s a product which sensorial quality is directly related to final commercial price, and so, increase such quality may mean an increase on coffee producer final income and such of entire coffee production region. Processing type plays an important role on final sensorial quality, and on this context, fermentation step stands out on quality changes. On this work, were studied the arabica coffee’s final sensorial quality and physicochemical characteristics, of a Yellow Catuai IAC 62, produced on Carmo do Paranaiba (Minas Gerais State) Region. Coffee fruits were handpicked, only ripe yellow cherries were selected, inoculated with Saccharomyces cerevisiae for fermentation. An experimental design were done by a Composite Central Rotational Design (CCRD) to evaluate fermentation process related to fermentation time and temperature and getting as responses fermentative mass pH, fruit moisture (just as process were conducted), sugars and organic acids content (HPLC) and sensorial quality by Specialty Coffee Association (SCA) on two different roasts levels (light medium roast and medium roast). There were determined fit equations to final coffee scores, on both roasts’ levels providing a first step for field process optimization. Independent of test (from – α to + α), it was observed that coffees, even in extreme time and temperature, behave sensorially similarly related to final scores (in general from 81 to 85 in SCA score table), being all of them classified as specialty coffees. Fructose content vary only with fermentation time and not with temperature, while sucrose and glucose contents decreased while time and temperature advances. Glycerol was formed depending on both variables, and its content increase with time and temperature increase. pH behaved just as described by literature, decreasing with time advance, and more intensely as temperature increases. Organic acids such as acetic, propionic, succinic and lactic were measured at final fermentation. Sensorial evaluation attributes such aroma, uniformity, clean cup were not affected by different fermentation conditions not by roast level. Coffee drink’s acidity was affected by fermentation, mainly on light roasts tests, and increase of time seams to positively contribute for this attribute. Besides, more intense roasts levels seem to provoke acidity attribute score decrease. Attribute body were influenced by fermentation, but not by roast level, while residual taste was influenced by both. Drink balance was also affected by fermentation, and on more intense roast levels seems to influence it negatively. As for the global evaluation, higher fermentation temperatures increased this attribute scores, but roast influence couldn’t be determinate. By Main Component Analysis were possible to correlate aroma, flavor, body, residual taste, balance and final score as those ones with greater influence on contribution for coffee’s sensorial profile.